Genetic loci, rs17817449 and rs6567160, known for obesity and the risk of stroke events among middle-aged and older Chinese people - Zhong, Qiong-Qiong; Zhu, Feng (Frontiers in Neurology, 2022)
Background Fat Mass and Obesity-Associated (FTO) and the Melanocortin-4 Receptor (MC4R) genes are strongly associated with obesity, an established risk factor for stroke. We aimed to assess the associations between rs17817449 at the FTO and rs6567160 at the MC4R and the risk of stroke events in middle-aged and older Chinese people. Materials and methods Study data were obtained from the Guangzhou Biobank Cohort Study; a total of 148 participants with a self-reported history of stroke and an equal volume of age- and sex-matched participants were selected as the cases and the controls in a case-control study; a total of 13,967 participants at the first follow-up and all participants with fatal stroke (up to April 2021) were included in a retrospective cohort study. Conditional logistic regression and the Cox proportional hazards regression analyses were used to assess the associations of the two genetic loci with the risk of stroke events. Results After adjusting for age, sex, education, job, smoking, alcohol consumption, body mass index, physical activity, hypertension, diabetes, and dyslipidemia, rs17817449 and rs6567160 shared minor alleles G and C, respectively, in the case-control analyses. The genotypes GG+GT of rs17817449 at the FTO were significantly associated with a decreased risk of fatal stroke occurrence, with fatal all strokes having an adjusted hazard ratio (aHR) of 0.71 (95% confidence intervals (CI) 0.52-0.97, P = 0.04) and fatal ischemic stroke having an aHR of 0.64 (95% CI 0.41–1.00, P = 0.05), when the genotype TT was taken as a reference and a series of multiplicities were adjusted; the risk of fatal all strokes was lowered by dyslipidemia (aHR = 0.63, 95% CI 0.39–1.00, P = 0.05) and non–diabetes (aHR = 0.68, 95% CI 0.46–0.99, P = 0.049) in the retrospective cohort analyses. Significances were observed neither in the associations between rs6567160 and the risk of stroke events nor in an interaction between rs17817449 and rs6567160 in the two-stage analyses. Conclusion The G allele of rs17817449 at the FTO, not rs6567160 at the MC4R, was associated with a decreased risk of fatal stroke occurrence; its functional role in stroke should be explored in relatively healthy middle-aged to older Chinese people.